Geomorphological hazards susceptibility in high-density urban areas: a case study of Mexico City - García Soriano, Daniel (2020)
Developing countries face more impacts due to natural hazards because of rapid urbanization, natural resources overexploitation, and lack of territorial management. Mexico City is one of the most populated metropolitan areas of the world and in addition, due to its geophysical dynamics and increasing vulnerability, is frequently impacted by natural disasters. Every year, various natural hazards affect Iztapalapa district, the most densely populated political-administrative unit in Mexico, and represent a high risk for approximately two million inhabitants. We used various geomorphic analyses to develop a feasible methodology to reduce the disaster risk in Iztapalapa district. In order to understand the general geomorphic dynamic of Iztapalapa district, we defined three geomorphological regions: the lacustrine plain, the volcanic piedmont, and the mountain area. Afterwards, we developed a geomorphological mapping based on LiDAR and aerial photographs to obtain thirty landforms divided into endogenic and exogenic landforms, both erosional and depositional, at 1:20,000 scale. Based on these maps, we described four geomorphological hazard zonation for floods, subsidence, soil fractures, and rockfalls in Iztapalapa district. The higher occurrence of subsidence, soil fractures and floods are in the palustrine plains, while rockfalls are associated with volcanic slopes. This study provides important input for local and regional stakeholders on territorial and risk management. Moreover, this practical methodology can be applied in other countries to facilitate disaster risk assessments.